1995
DOI: 10.1111/1523-1747.ep12607024
|View full text |Cite
|
Sign up to set email alerts
|

βIG-H3, a Novel Secretory Protein Inducible by Transforming Growth Factor-β, Is Present in Normal Skin and Promotes the Adhesion and Spreading of Dermal Fibroblasts In Vitro

Abstract: We have previously identified a gene, beta ig-h3, which is highly induced in A549 cells (human lung adenocarcinoma) after growth arrest by transforming growth factor-beta. The beta ig-h3 gene encodes a 683-amino-acid secretory protein termed beta IG-H3, and treatment of several cell lines with transforming growth factor-beta results in increased secretion of beta IG-H3 into cell culture supernatants. In this report, we further characterize beta IG-H3 with respect to its synthesis and function. Primary human fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 35 publications
5
157
1
Order By: Relevance
“…Periostin has a typical signal sequence, followed by a cysteine-rich domain, four repeated and conserved domains and a C-terminal hydrophilic domain (Takeshita et al, 1993;Horiuchi et al, 1999). A similar structure was reported for fasciclin I, a cell adhesion molecule involved in the development of the central nervous system of insects (Zinn et al, 1988), and for the big-h3 molecule, a secreted protein induced by TGF-b1 which promotes the attachment and spreading of fibroblasts (Skonier et al, 1992;LeBaron et al, 1995). Periostin was found to be overexpressed in various types of human cancer such as lung (Sasaki et al, 2001a), brain (Sasaki et al, 2002), ovary (Gillan et al, 2002), breast (Shao et al, 2004) and colon cancers Tai et al, 2005) and elevated levels have been detected in sera of patients with thymoma (Sasaki et al, 2001b), non-small lung carcinoma (Sasaki et al, 2001c) and breast cancer (Sasaki et al, 2003).…”
Section: Introductionmentioning
confidence: 68%
“…Periostin has a typical signal sequence, followed by a cysteine-rich domain, four repeated and conserved domains and a C-terminal hydrophilic domain (Takeshita et al, 1993;Horiuchi et al, 1999). A similar structure was reported for fasciclin I, a cell adhesion molecule involved in the development of the central nervous system of insects (Zinn et al, 1988), and for the big-h3 molecule, a secreted protein induced by TGF-b1 which promotes the attachment and spreading of fibroblasts (Skonier et al, 1992;LeBaron et al, 1995). Periostin was found to be overexpressed in various types of human cancer such as lung (Sasaki et al, 2001a), brain (Sasaki et al, 2002), ovary (Gillan et al, 2002), breast (Shao et al, 2004) and colon cancers Tai et al, 2005) and elevated levels have been detected in sera of patients with thymoma (Sasaki et al, 2001b), non-small lung carcinoma (Sasaki et al, 2001c) and breast cancer (Sasaki et al, 2003).…”
Section: Introductionmentioning
confidence: 68%
“…Periostin from osteoblasts was originally identified to function as a cell adhesion molecule for preosteoblasts and precipitate in osteoblast recruitment, attachment and spreading. 16,17 Recently, proteomic and microarray profiling studies showed that periostin is up-regulated in pancreatic cancer tissues. [18][19][20] However, it has been demonstrated that periostin protein was mainly detected in the juxtatumoral stroma components, while the tumor cells themselves showed no immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first evidence that Betaig-h3 gene has tumour suppressor function in a human epithelium-derived tumour model. Betaig-h3 is a secreted protein that promotes the adhesion of dermal fibroblasts and corneal epithelial cells (LeBaron et al, 1995;Billings et al, 2000a,b;). These findings imply that Betaigh3 gene affects cell -ECM interaction by regulating integrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that Betaig-h3 protein affect cell -ECM interaction through regulation of integrin receptor (LeBaron et al, 1995;Billings et al, 2000a,b). Using cDNA array, it was found The blots were hybridised to 32 P-labelled Betaig-h3 cDNA probes.…”
Section: Betaig-h3 Gene Is Related To the Expression Level Of Integrimentioning
confidence: 98%
See 1 more Smart Citation